Transformative Court-Annexed Mediation in Divorce Cases: A Legal System Perspective on the 100% Settlement Rate at the Tondano Religious Court - Muhammady, Alfian; Enhasiwi, Bijak; Awaliah, Sofwatun (Antmind Review: Journal of Sharia and Legal Ethics, 2025)
Court-annexed mediation has been institutionally mandated in Indonesian Religious Courts to reduce divorce rates and promote family reconciliation; however, empirical evidence consistently shows low success rates in most jurisdictions. This study examines an exceptional case of mediation effectiveness at the Tondano Religious Court, where divorce mediation achieved a 100% settlement rate between January and June 2025. Employing a qualitative normative-empirical approach with a case study design, data were collected through in-depth interviews with certified mediator judges, litigating parties, court observations, and analysis of mediation reports and case files. The findings reveal that the success of mediation at the Tondano Religious Court was not merely the result of formal compliance with Supreme Court Regulation (PERMA) No. 1 of 2016, but rather the outcome of transformative mediation practices supported by an integrated legal system. These practices include strong mediator professionalism and ethical commitment, empathetic and psychologically informed mediation approaches, the incorporation of religious and local cultural values, flexible mediation duration, and a supportive institutional environment. Using Lawrence M. Friedman’s legal system theory, this study demonstrates that the convergence of legal structure, legal substance, and legal culture played a decisive role in achieving mediation effectiveness. The study argues that mediation in this context functions not only as a procedural requirement, but as a substantive and ethical mechanism for dispute resolution. This article contributes to the discourse on Islamic legal ethics and judicial reform by offering a scalable model of effective mediation that aligns legal norms with social and cultural realities in plural societies.